Perlindungan Hukum Terdahap Korban Tindak Pidana Perdagangan Orang “Pidana Eksploitasi Orang” (Studi kasus Putusan Nomor 608/Pid.Sus/2023/PN Jmr) - Fatimatus Zahro; Dairani Dairani; Ahmad Yunus (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The crime of trafficking in persons or the crime of exploitation of persons is a crime that violates human rights and is increasingly prevalent in Indonesia, where the crime of trafficking in persons or the crime of exploitation of persons is very threatening to the life and environment of the community and the state, the problem discussed is the purpose and modus operandi of the crime of trafficking in persons or the crime of exploitation of persons, and a form of legal protection for victims of human trafficking. The formulation of the problem studied is related to the modus operandi that often occurs today, especially in Indonesia in these crimes. How is it related to the form of protection and rehabilitation and the fulfillment of restitution for victims of human trafficking. This research is included in the research of normative juridical law (Legal Reasherc), legislative approaches, philosophical approaches, and historical approaches which are also strengthened by court decisions which has permanent legal force. The modus operandi of the crime of human trafficking is through persuasion or seduction with the promise of being given a well-established and guaranteed job with their safety while working as well as the lure of high salaries so that the victims of human trafficking without thinking long immediately agree to this, this researcher also discusses the legal protection for victims of human trafficking or the crime of exploitation of persons contained in Law Number 21 of 2007 concerning The eradication of the crime of trafficking in persons must be implemented and maximized again related to the protection and fulfillment of the rights of victims of trafficking in persons.